165k views
4 votes
Simplify and then evaluate the equation when A=2 and b=4

Simplify and then evaluate the equation when A=2 and b=4-example-1

1 Answer

4 votes

we have the equation


b^2+3(b-b^2)-2a

Remove the parenthesis and apply the distributive property


b^2+3b-3b^2-2a

Combine like terms


-2b^2+3b-2a

For a=2 and b=4

substitute


\begin{gathered} -2(4)^2+3(4)-2(2) \\ -32+12-4 \\ -24 \end{gathered}

the answer is -24

User Jude Osbert K
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.